Journal of Marine Science and Application - Duan, Wenyang; Guedes Soares, Carlos; SpringerLink (Online service) (Harbin : Harbin Engineering University : Imprint: Harbin Engineering University, co-published with Springer.)
The aim of the JMSA is to provide a platform for current issues in a range of topics relevant to marine science and engineering, and to guide engineering application for scientists and engineers. JMSA is a scholarly international journal, publishing high-level peer-reviewed research on the subjects in the field of theoretical and experimental investigations, that explore naval architecture, ocean engineering, marine renewable energy, underwater technology, marine engineering, corrosion prevention, ocean acoustics, automatic navigation among others. Topics include, but are not limited to: Naval architecture Marine hydrodynamics Structural mechanics Design methodology & practice Ship resistance and propulsion Safety and reliability Marine equipment technology Ocean engineering Coastal engineering Offshore engineering Marine drilling Pipelines and risers Cable, mooring, buoy technology Marine renewable energy Offshore wind energy utilization Ocean wave energy utilization Ocean current energy utilization Underwater technology Underwater vehicles Underwater explosion Ocean resources & mining Marine sensors Marine engineering Marine engines and fuels Marine power engineering Vibration and noise control Heat transfer and fluid flow Ocean acoustics Sonar and transducers Sound propagation and scattering Acoustical oceanography Signal coherence and fluctuation Polar and arctic engineering Design of ice-going ships Arctic structures Ice loads and simulation of ice Marine environmental engineering Oil spill prevention Maine pollution modeling Marine corrosion and protection Corrosion and deterioration modeling Ship corrosion protection Pipeline corrosion protection Automatic navigation Ship navigation system Marine navigation equipment System dynamics & control Marine science Marine meteorology Ocean internal waves Extreme offshore environments Experimental technology of above Engineering application of above The journal welcomes submissions of papers around the world on all the above topics. It also receives original works in the other emerging and interdisciplinary areas of the oceans.
Keywords: Geotechnical engineering; Machinery; Building construction; Power electronics; Offshore Engineering; Machinery and Machine Elements; Power Electronics, Electrical Machines and Networks; Geotechnical Engineering & Applied Earth Sciences